The Roles of Serotonin in Neuropsychiatric Disorders - Pourhamzeh, Mahsa; Moravej, Fahimeh Ghasemi; Arabi, Mehrnoosh; Shahriari, Elahe; Mehrabi, Soraya; Ward, Richard; Ahadi, Reza; Joghataei, Mohammad Taghi (Cellular and molecular neurobiology, 2022)
The serotonergic system extends throughout the central nervous system (CNS) and the gastrointestinal (GI) tract. In the CNS, serotonin (5-HT, 5-hydroxytryptamine) modulates a broad spectrum of functions, including mood, cognition, anxiety, learning, memory, reward processing, and sleep. These processes are mediated through 5-HT binding to 5-HT receptors (5-HTRs), are classified into seven distinct groups. Deficits in the serotonergic system can result in various pathological conditions, particularly depression, schizophrenia, mood disorders, and autism. In this review, we outlined the complexity of serotonergic modulation of physiologic and pathologic processes. Moreover, we provided experimental and clinical evidence of 5-HT’s involvement in neuropsychiatric disorders and discussed the molecular mechanisms that underlie these illnesses and contribute to the new therapies.